Micronutrients in infants suffering from cow’s milk allergy fed with dietary formulas and breast milk - Shohreh Maleknejad; Kobra Dashti; Afshin Safaei-Asl; Zahra Atrkar Roshan; Soodeh Salehi; Afagh Hassanzadeh-Rad (BMC Pediatrics, 2024)
Abstract Introduction Cow’s milk allergy (CMA) is the most common food allergy in infants. As this food allergy indicates a wide range of clinical syndromes due to immunological reactions to cow’s milk proteins, we aimed to evaluate the status of micronutrients in infants suffering from cow’s milk allergy. Methods In this historical cohort study, infants with CMA were divided into two equal groups: breastfeeding and diet formula feeding. Data were gathered by a form, including the micronutrients such as iron, selenium, calcium, phosphorus, zinc, and vitamin D. Groups were compared and data were analyzed by the IBM SPSS version 21. Results This study involved 60 six-month-old infants, and the findings revealed no significant difference between the two groups concerning magnesium, phosphorus, zinc, and vitamin D. However, infants in the formula-feeding group exhibited significantly elevated mean serum levels of iron and selenium, whereas breastfed infants displayed higher levels of calcium. Conclusion The findings of this research revealed a significant difference in calcium, selenium, and iron levels between formula-fed and breastfed infants, even though all variables were within the normal range for both groups. In light of these results, conducting further studies with a larger sample size and extended follow-up periods becomes imperative.